Recent Applications of Ionic Liquids in Organocatalytic Processes - Herradon, Bernardo; Mann, Enrique (Current Organocatalysis, 2015)
In this review, we report an overview of some recent applications of ionic liquids in diverse organocatalyzed transformations such as, for example, the conjugate addition, Diels Alder and the aldol type reactions. Examples of ionic liquids acting both as catalyst (“nonsolvent applications”) and as reaction media are described. The interesting potential applications resulting of the merging of two such active research areas as ionic liquids and organocatalysis are only just starting to be explored by the synthetic organic chemists.
Keywords: ionic liquid